The expression (-2 - 6i)-(-2-4i) to a + bi form is 0 - 2i.
Complete question.
Simplify the expression to a + bi form:
(-2 - 6i)-(-2-4i)
Square root of any negative number are expressed as a complex number. For example i = √-1
Complex numbers are generally written in the format z = x+iy
Given the expression (-2 - 6i)-(-2-4i)), in expansion:
(-2 - 6i)-(-2-4i)
= -2 - 6i + 2+4i
Collect the like terms
= (-2 + 2) - 6i + 4i
= 0 - 2i
Therefore the expression (-2 - 6i)-(-2-4i) to a + bi form is 0 - 2i.
Learn more on complex number here: brainly.com/question/12375854
-8 = trevon
(3/4)-8 = beth
= -6
1/4[(3/4)-8] = leah
1/4(-6)
= -1.5
4 x (3+6) = 12 + 24 ---->Distributive
3 + ( 8 + 2) = 3 + (2 + 8) ---> Commutative
6 x (7 x 3 ) = (6 x 7 ) x 3 --->Associative
Answer:
yes
Step-by-step explanation:
Answer:
what is Never Have I Ever
Step-by-step explanation: